Chlamydospore dormancy and predatory activity of nematophagous fungus Duddingtonia flagrans - Wang, Bo‐bo; Li, You‐lei; Tian, Shu‐yue; Wang, Hai‐zhou; Li, Xin; Wang, Feng‐hui; Cai, Kui‐zheng (Journal of basic microbiology, 2024)
The chlamydospores of Duddingtonia flagrans are an essential survival and reproductive structure and also an effective ingredient for the biocontrol of parasitic nematodes in livestock. In this study, entering and exiting dormancy conditions and predatory activity of the fungal chlamydospores were conducted. During this fungal growth process, the cultivation time is negatively correlated with spore germination rates. After the spores were processed by vacuum drying for 168 h, their germination rate dropped to 0.94%. In contrast, the percentage of living spores remained 54.82%, suggesting that the spores entered structural dormancy in the arid environment. Meanwhile, the efficacies of the spore against Haemonchus contortus larvae were 93.05% (0 h), 92.19% (16 h), 92.77% (96 h), and 86.45% (168 h), respectively. After dormant spores were stored at 4°C, −20°C, and 28°C (RH90 ~ 95%) for 7 days, their germination rate began to increase significantly (p < 0.05). For in vitro predation assay under the condition of 28°C (RH90 ~ 95%), the predation rate was significantly higher on the 7th day after incubation than that on the 3rd day (p < 0.05). During the period when spores were stored at room temperature for 8 months, their germination rate decreased in the first 5 months and then increased slowly to reach a peak in the 7th month. However, the reduction rate of H. contortus L3 in feces captured by spores remained above 71% for the first 7 months. These results will help us increase the end products yield and the quality of biological control of parasitic nematodes in livestock.